Greenhouse Gas (GHG) Emission Estimation from Cropland Remaining Cropland in AFOLU Sector for Various Districts in Sarawak - Peng, E. K.; Malek, M. A.; Bahrum, N. Azimah; Tan, C. S. (International Journal of Engineering and Technology, 2018)
Greenhouse gases (GHG) exist in the world and lead to more heat being trapped. The study belongs to part of initiatives to establish GHG emission from Agricultural Forest Land Use (AFOLU) at Sarawak, Malaysia. The study implements Tier 1 methodology of 2006 IPCC (Intergovernmental Panel on Climate Change) Guidelines to estimate carbon dioxide (CO2) emissions from cropland remaining cropland in Sarawak, in which uncertainty analyses are included. The study aids in establishing the quantity as well as trending of CO2 emissions from crops such as fruit trees, cocoa, pepper, rubber and palm oil cultivated in non-urban and non-rural areas of Sarawak from year of 2008 to 2012. Based on this study, it is found that Miri is the highest CO2 emitter from palm oil as compared to other districts with total amount of 681.55 kt C/year. It is also found that CO2 emission from crops cultivated in Limbang (non-urban) is the lowest with total values of 35.84 kt C/year, 16.16 kt C/year, 0.13 kt C/year and 5.08 kt C/year for palm oil, rubber, pepper and fruit trees respectively. Generally, results obtained from this study showed that at most districts in Sarawak, palm oil plantations produce the highest CO2 emission demonstrating increasing trend through-out the study duration, while the rubber plantations ranked second. Estimated emission values of CO2 can be used for planning and mitigation purposes at various level of confidence.
Keywords: 2006 IPCC Guidelines; carbon dioxide (CO2); cropland remaining cropland; Greenhouse gas (GHG); Sarawak